PERAN ISTRI PEKERJA PERSPEKTIF MUI KABUPATEN BANYUWANGI (STUDI KASUS BURUH PABRIK SARDEN PT PASIFIK HARVEST INDONESIA) - M. Ainul Yaqin; Akhmad Rudi Maswanto; Ansari Ansari (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This research aims to examine the role of wives of sardine factory workers at PT Pasifik Harvest Indonesia in Badean Village, Blimbingsari District, Banyuwangi Regency, as breadwinners, viewed from the perspective of the Indonesian Ulema Council (MUI) of Banyuwangi Regency. This research uses an empirical research design with a descriptive qualitative method and a case study approach. Primary data was obtained through interviews with female factory workers and MUI clerics, while secondary data was sourced from verses of the Al-Qur'an, hadith, and relevant scientific journals. Data validity was tested using the triangulation method. The research results indicate that the wife's decision to work as a factory worker is driven by economic factors, namely the husband's income, which is felt to be insufficient for living needs and children's education costs, as well as environmental factors and work habits. Working provides an opportunity for wives to contribute to the family's economic welfare and prepare for future savings, although it also poses challenges in the form of limited time with children and partners, which can potentially disrupt household harmony. According to the view of the MUI clerics of Banyuwangi Regency, the law for a wife working is fundamentally permissible as long as it does not contradict Islamic law, such as continuing to maintain modesty (aurat) and avoiding excessive mixing (ikhtilat), and is based on deliberation and the husband's permission with mutual understanding. This research confirms that the wife's role as an additional breadwinner can be in harmony with Islamic values if based on communication, agreement, and professionalism (itqan) between husband and wife.